Intrinsic healing response of the human anterior cruciate ligament: An histological study of reattached ACL remnants. Issue 2 (5th November 2013) - Nguyen, Duy Tan; Ramwadhdoebe, Tamara H.; van der Hart, Cor P.; Blankevoort, Leendert; Tak, Paul Peter; van Dijk, Cornelis Niek
ABSTRACT A reattachment of the tibial remnant of the torn anterior cruciate ligament (ACL) to the posterior cruciate ligament is sometimes observed during surgery and apparently implies that the human ACL does have a healing response. The aim of this study was to investigate whether this reattachment tissue has similar histological characteristics of a healing response as the medial collateral ligament (MCL), which can heal spontaneously. Standard histology and immunostaining of α‐smooth muscle actin and collagen type 3 was performed. The results shows that the reattached tissue has typical characteristics of a healing response: the reattached ACL remnant could not be released by forceful traction; microscopy showed that the collagen fibers of the reattached tissue were disorganized with no preferred direction; increased neovascularization; the presence of lipid vacuoles; the mean number of cells within the biopsy tissue was 631 ± 269 cells per mm2; and 68 ± 20% was expressing α‐SMA; semi‐quantitative analysis of collagen type 3 expression showed that collagen type 3 had an high expression with an average score of 3. In conclusion, this study shows that the human proximal 1/3 ACL has an intrinsic healing response with typical histological characteristics similar to the MCL. © 2013 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 32:296–301, 2014.